Analysis of Promotion on The Mediana Sumedang - Kartiwa, Aa; Rokayah, Cicih Siti; Sunarso, Dede Toto; Fathurrohman, Hefni; Nugraha, Dede Iman; Hernasari, Kirey Desira (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2024)
Promotion strategy is planning a series of activities to choose and implement the right promotion method for the company. The focus of the research in this study is to analyze the promotion strategy at Mediana Sumedang through the elements of the promotion mix. Which has the aim of knowing the promotional strategies carried out by Mediana Sumedang and knowing the obstacles and solutions to the promotion strategy at Mediana Sumedang. The research method used is using qualitative research methods where the method based on the philosophy of postpositivism is used to examine the condition of natural objects, where the researcher is the key instrument. While the activities in data analysis begin with data collection, data reduction, data display, and conclusion drawing/verification. From the results of research and discussion, it can be concluded that Mediana's promotional strategy is quite good by using all promotional elements such as advertising, sales promotion, public relations, personal selling and direct/online marketing. The obstacle faced by Mediana Sumedang is the number of competitors that make customers switch to competitors. The solution is to give discounts to customers and participate in social activities such as events or sponsorships to introduce Mediana to the public